A Sociological Analysis of the Effect of Social Capacity-Building on the Social Participation of Female Heads of Household in Activities Related to the Country’s Economic Development (A Study Based on the Grounded Theory Approach) - Fatehi Jifrudi, Arezoo; Mirzaei, Khalil; Fatehi, Hamid Reza (Management Strategies and Engineering Sciences, 2026)
The purpose of this study is to conduct a sociological analysis of the effect of social capacity-building on the social and economic participation of female heads of household covered by the Welfare Organization of Tehran Province. The study examines various dimensions of social capacity-building, identifies the obstacles and challenges ahead, and ultimately provides practical strategies for empowering this group and facilitating their role in economic development. Methodologically, the research adopted a qualitative approach and employed the grounded theory method. The statistical population consisted of economic and social experts familiar with issues concerning women. Participants were selected through purposive sampling based on the criterion of theoretical saturation, resulting in a final sample size of 14 individuals. The primary data collection instrument was the semi-structured interview, and the obtained data were analyzed through three stages of open, axial, and selective coding, culminating in the development of a paradigmatic model. The key findings derived from the interview analyses indicated that the two categories of “empowerment strategies” (33.10%) and “economic development” (34.15%) were the most frequent and thus the most significant concepts. This demonstrates that the path to achieving economic development becomes smoother through focusing on practical empowerment solutions (such as training, networking, and access to resources). In contrast, “macro-level challenges” (11.27%)—structural, cultural, and psychological—were identified as the main obstacles. The final model of the research shows that social capacity-building strengthens social and economic participation through mediating mechanisms of reducing barriers and enhancing capabilities, although the intensity of this relationship is influenced by intervening factors such as macro-policies and structural challenges. Based on the above findings, it can be concluded that empowering female heads of household and increasing their participation requires an integrated program that simultaneously focuses on the micro level (strengthening individual skills), the meso level (strengthening local institutions and networks), and the macro level (reforming laws and policies). Moreover, the low rate of “scientific-executive foundations” (1.06%) in the findings underscores the need for greater attention to action-oriented research and the practical application of produced knowledge for policymakers and planners.